Long Head of the Biceps Pathology Combined with Rotator Cuff Tears. (19th November 2012) - Ditsios, Konstantinos; Agathangelidis, Filon; Boutsiadis, Achilleas; Karataglis, Dimitrios; Papadopoulos, Pericles
Abstract : The long head of the biceps tendon (LHBT) is an anatomic structure commonly involved in painful shoulder conditions as a result of trauma, degeneration, or overuse. Recent studies have pointed out the close correlation between LHBT lesions and rotator cuff (RCT) tears. Clinicians need to take into account the importance of the LHBT in the presence of other shoulder pathologies. This paper provides an up-to-date overview of recent publications on anatomy, pathophysiology, diagnosis, classification, and current treatment strategies.